Condition monitoring of induction motors via instantaneous power analysis - Irfan, M. (Springer New York LLC, 2017)
Condition monitoring is an important factor in assuring the well-being of motors. Existing approaches of condition monitoring require access to the motor for sensor installation. This paper reviews various forms of existing condition monitoring methods and highlights the need for an economical intelligent fault diagnosis system. In this study, the methodology taken in developing a condition monitoring system for motor bearing fault identification, utilizing the commonly available motor stator current and voltage is demonstrated. This unique diagnostic condition monitoring system provides continuous real time tracking of the various bearing defects and determines the fault severity which can be adopted for fast decision making. The study on different bearing faults under no-load and full-load conditions was carried out experimentally and then analyzed. The results on the real hardware implementation have confirmed the effectiveness of the proposed approach. © 2015, Springer Science+Business Media New York.